2005
DOI: 10.1038/sj.leu.2403817
|View full text |Cite
|
Sign up to set email alerts
|

Wilms' tumour gene 1 (WT1) in human neoplasia

Abstract: The transcription factor Wilms' tumour gene 1 (WT1) is important as a prognostic marker as well as in the detection and monitoring of minimal residual disease in leukaemia and myelodysplastic syndromes. Evidence has accumulated over the past decade to show that WT1 is a key molecule for tumour proliferation in a large number of human neoplasms most prominent in acute leukaemias, making it a suitable target for therapeutic strategies. Based on animal results, showing safety and efficacy of immunization with WT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 43 publications
0
68
0
Order By: Relevance
“…In contrast, overexpression of the non-mutated Wilms' tumor gene 1 (WT1) is found in 89-100% 10,[17][18][19][20] of patients with AML and MDS, making this marker an ideal tool for monitoring MRD. WT1 expression has already been shown to be a helpful marker in patients with AML after chemotherapy, 19,[21][22][23] after autologous 24 and after conventional allogeneic HCT.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, overexpression of the non-mutated Wilms' tumor gene 1 (WT1) is found in 89-100% 10,[17][18][19][20] of patients with AML and MDS, making this marker an ideal tool for monitoring MRD. WT1 expression has already been shown to be a helpful marker in patients with AML after chemotherapy, 19,[21][22][23] after autologous 24 and after conventional allogeneic HCT.…”
Section: Introductionmentioning
confidence: 99%
“…The precise role of WT1 in hematopoiesis and its contribution to leukemogenesis are still uncertain, although it has been suggested that impairment of WT1 protein function could promote stem cell proliferation and induce a differentiation block of hematopoietic cells. 164,165 WT1 gene is highly expressed in various types of leukemias, particularly in AML, and therefore can be used for MRD monitoring in AML patients. Mutations in WT1 gene in AML were first reported in 1998 by King-Underwood et al 166 in about 10-15% of AML cases.…”
Section: Other Mutated Genesmentioning
confidence: 99%
“…The gene product, WT1, represses the transcription of growth factors, growth factor receptors and other genes. [1][2][3] On the other hand, WT1 has been regarded as an oncogene for leukemia and some solid tumors because high expression levels of WT1 mRNA were observed in these diseases, and in vivo and in vitro studies showed the positive roles it plays in cell growth and transformation. [4][5][6][7][8] WT1 mRNA is reportedly a good clinical marker for disease progression, diagnosis and detection of the minimal residual diseases of myelodysplastic syndromes and leukemia.…”
Section: Introductionmentioning
confidence: 99%